2013
DOI: 10.4103/0972-0707.114362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of home bleaching on surface hardness and surface roughness of an experimental nanocomposite

Abstract: Objective:Home bleaching agents may not be safe for composite resins. The purpose of this study was to evaluate the effects of 10 and 20% Opalescence® PF home bleaching agents on the surface roughness and hardness of universal nanocomposite (Filtek Z350), anterior nanocomposite (KeLFiL), and nanohybrid composite (TPH 3).Materials and Methods:Fifty-four composite resin samples with 18 samples for each type of composite resin were prepared using acrylic molds (4 × 2 mm). Each type of composite resin was further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 16 publications
2
40
0
Order By: Relevance
“…14,15,17,29,33,34 Findings of a decrease in microhardness are consistent with several additional studies. 13,14,35,36,37 Although a reduced microhardness was found, there was controversy regarding whether this is limited to the composite surface layers and can be removed with post-operative re-polishing 13,38 or if the damage extends deeper. One study observed softening of sub-surface layers and concluded that it is unlikely that post-operative polishing is sufficient to reverse the damage.…”
Section: Compositementioning
confidence: 99%
“…14,15,17,29,33,34 Findings of a decrease in microhardness are consistent with several additional studies. 13,14,35,36,37 Although a reduced microhardness was found, there was controversy regarding whether this is limited to the composite surface layers and can be removed with post-operative re-polishing 13,38 or if the damage extends deeper. One study observed softening of sub-surface layers and concluded that it is unlikely that post-operative polishing is sufficient to reverse the damage.…”
Section: Compositementioning
confidence: 99%
“…It has been reported that about 40% of people have at least one repair in their mouth (7). Also, composites, as tooth isochromatic materials, have been welcomed by the public and are used widely in dental restoration (5). Thus, it is necessary to investigate the treatment effect of bleaching on composite properties in order to select the best treatment for the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hardness is defined as resistance of a material against depression or penetration of other materials (8). Results of various studies about composites microhardness after bleaching have reported a decrease in hardiness (2,3,5,7,9,(12)(13)(14)(15)(16), increase in hardiness (14,(17)(18)(19) or no significant change (3,8,(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 In patients with poor oral hygiene and a cariogenic diet, giomer might be a good choice for decreasing the effects of a poor oral environment due to its capacity to release fluoride and high polishability. 20,21 In addition, some studies have shown that SR of restorative materials increases after bleaching with carbamide peroxide. [22][23][24][25][26] Mohammadi et al, 27 too, showed a statistically significant difference in the SR of giomer before and after bleaching with carbamide peroxide.…”
Section: Introductionmentioning
confidence: 99%